Innovation in green energy technologies and the economic performance of firms - Jürgen Kruse (Institute of Energy Economics at the University of Cologne (EWI), 2016)
In this article, I empirically analyze and compare the impact of innovation in green and non-green energy technologies on the economic performance of firms. My analysis is conducted on a panel of 8,619 patenting firms including 968 green energy patenters from 22 European countries over the period 2003 to 2010. I measure economic firm performance in terms of productivity and use a panel data model based on an extended Cobb-Douglas production function. My results show that green energy innovation has a statistically significant negative impact on economic firm performance. In contrast, nongreen energy innovation is shown to have a statistically significant positive impact on economic firm performance. These findings suggest that private economic returns in terms of productivity are lower for green energy than for non-green energy innovation.
Keywords: C33; L25; O31; Q40; Q55; 330; green energy technologies; innovation; performance; patents; technological change